ANALISIS PENGARUH KOMPENSASI TERHADAP PRODUKTIVITAS KERJA KARYAWANCOCA-COLA INDONESIA - Lite Lite (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2017)
There is a universal awareness on the importance of productivity in improving national welfare. The productivity is an essential factor in maintaining and developing the success of an organization. So that a company can achieve its goals one of which to improve the work productivity, then it is an obligation for the leaders to provide motivation for the employees in the form of compensation.This research is willing to achieve the goals namely (1) to determine the effects of salary, intensive, facility, position promotion and work environment on the work productivity of CocaCola Indonesia employees either simultaneously or partially (2) to determine the most influential factors on the work productivity of CocaCola Indonesia employees.In this research, the population is all of the employees in production section CocaColaIndonesia. There are 130 employees as the research samples. The sample collection technique is bypurposivesampling   technique. The data analysis tools used in this research are validity, reliability, classical assumption test, multiple regression, determination coefficient and hypothesis testing.Results of the research are (1) There are effects of salary on the employee work productivity (2)There are effects of incentive on the employee work productivity (4) There are effects of work environment on the employee work productivity (5) There are significant effects of salary (X1),incentive (X2)allowances (X3),facility (X4), position promotion (X5) and work environment (X6) simultaneously on the work productivity (Y). The salary has the dominant effects on the work productivity namely by b1=0,248.